2014
DOI: 10.1080/13102818.2014.911611
|View full text |Cite
|
Sign up to set email alerts
|

Chinese medicinal formula Fufang Xueshuantong capsule could inhibit the activity of angiotensin converting enzyme

Abstract: Fufang Xueshuantong (FXST) capsule, a Chinese medicinal formula composed of four herbals – Panax notoginseng, Radix Astragali, Radix Salvia Miltiorrhizae and Radix Scrophulariaceae, has been used to treat cardiovascular diseases for many years, but the pharmacological mechanisms underlying its effects has not been clarified. This study investigates if a connection between FXST and angiotensin converting enzyme (ACE) might be an explanation for its pharmacological effects. ACE inhibition assay was performed on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Previous studies have demonstrated that by binding to the effects of anti-inflammatory properties, reducing blood viscosity, and antiapoptosis, ginsenosides treatment has outstanding advantage in therapy of neurological disorders accompanied with cognitive impairment ( Liu et al, 2014 , 2018 ; Sheng et al, 2014 ; Zhong et al, 2015 ). For example, individuals with a commonly occurring brain disorder, traumatic brain injury, characterized by intracranial/intracerebral hemorrhage ( Regan et al, 2018 ), generally develop symptoms of cognitive deficit ( Ratliff et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that by binding to the effects of anti-inflammatory properties, reducing blood viscosity, and antiapoptosis, ginsenosides treatment has outstanding advantage in therapy of neurological disorders accompanied with cognitive impairment ( Liu et al, 2014 , 2018 ; Sheng et al, 2014 ; Zhong et al, 2015 ). For example, individuals with a commonly occurring brain disorder, traumatic brain injury, characterized by intracranial/intracerebral hemorrhage ( Regan et al, 2018 ), generally develop symptoms of cognitive deficit ( Ratliff et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The current findings are consistent with the results of studies in animal models. 28 30 The following alternative treatment strategies have yielded inconsistent results: combination therapy with photodynamic therapy, 33 core vitrectomy, 34 epimacular brachytherapy, 35 low-dose transpupillary thermotherapy, 36 switch to biweekly anti-VEGF dosing or algorithms, 37 adjunct pharmacologic treatment with intravitreous corticosteroids, 38 omega-3 supplementation, 39 and topical dorzolamide-timolol eyedrops. 40 As expected, intravitreal ranibizumab treatment alone induced significant functional and morphological improvement, as reported previously.…”
Section: Discussionmentioning
confidence: 99%
“… 27 The bioactive components of cFXST that ameliorate circulatory dysfunction have been identified. 28 30 These components influence serum proteins (e.g., von Willebrand factor, plasma fibrinogen, and antithrombin III), thereby attenuating erythrocyte aggregation, plasma viscosity enhancement, and acellular vessel formation. However, randomized controlled clinical studies related to the etiology of cFXST are lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the meridian theory of TCM, Fufang Xueshuantong (FXT) capsule was originally formulated twenty years ago and also has been accepted in 2003 by the State Food and Drug Administration of China for treatment of stable angina pectoris and retinal vein occlusion [ 115 , 116 ]. Fufang Xueshuantong (FXT), also known as compound Xueshuantong, is a Chinese herbal formula that consists of four traditional plants, namely Astragalus membranaceus, Scrophularia ningpoensis, P. notoginseng and Salvia miltiorrhiza [ 117 ].…”
Section: Recent Evidences Of Traditional Medicinal Plants In Diabementioning
confidence: 99%